Is there a Valid and Reliable Assessment of Diagnostic Knee Arthroscopy Skill? - Olson, Tyson; Koehler, Ryan; Butler, Aaron; Amsdell, Simon; Nicandri, Gregg (Clinical orthopaedics and related research, 2013)
Background The Basic Arthroscopic Knee Skill Scoring System (BAKSSS) has construct validity as an objective measure of arthroscopic proficiency when used to assess the task of performing arthroscopic meniscectomies on cadaver knees. The reliability of this instrument is unknown. Questions/purpose We asked whether (1) a simple modification of the BAKSSS would show construct validity similar to that in the initial BAKSSS study, (2) this assessment would be reliable, and (3) this assessment could be used as a high-stakes pass or fail test. Methods Twenty-three orthopaedic residents performed diagnostic knee arthroscopies on cadaveric knee specimens. Their competency was assessed by three live raters using the modified BAKSSS. Interrater reliability was assessed by comparing the scores given by each rater to each subject. Results The modified BAKSSS showed construct validity with junior residents achieving lower scores (mean score, 20) than senior residents (mean score, 33). The modified BAKSSS had an interrater reliability of kappa = 0.685–0.852. The modified BAKSSS had a kappa = 0.543 when used as a proficiency test for diagnostic arthroscopy. Conclusions The modified BAKSSS is useful for assessing diagnostic knee arthroscopy proficiency. Future scoring systems should be designed to be generalizable so they can be applied to multiple procedures without the need for modification, allow for video-based assessment, and must be rigorously tested for reliability and other types of validity (eg, face validity, content validity, and criterion-related validity). Clinical Relevance Having a valid and reliable assessment of basic arthroscopic procedures may allow educators to more adequately evaluate individual residents and the effectiveness of various training modalities.